The Crested Ibises expanding to plain areas exhibit a higher tolerance of human proximity - Yuqi Zou; Yiting Jiang; Zitan Song; Xiaobin Fang; Changqing Ding (Avian Research)
Animals must strike a balance between anti-predation behavior and other essential behaviors, such as foraging. Within the same species, strategies may vary on individuals' risk-taking preferences, and in this process the environment is a determinant, in addition to predator regime. The Crested Ibis (Nipponia nippon) exhibits such tendency. This is an endangered species, once inhabiting exclusively in China's Qinling Mountain. This used to be the sole remaining wild population. However, over recent decades, this population has expanded. A portion has relocated to breed in the lower plain area, which is characterized by elevated level of human activities and landscape complexity. We used flight initiation distance (FID) as an indicator of the ibises' risk-taking preference, particularly their response to human proximity. Additionally, we examined the environmental factors influencing their foraging site selection, including altitude, terrain openness, human activity intensity and human construction. Our findings revealed a significantly shorter FID among individuals relocating to plain habitats, indicating a higher tolerance of human proximity. The results showed that FID decreased with distance to the nearest human settlement. Another finding is that FID was independent of instant human activity intensity and environmental factors (altitude and terrain openness). These different may arise from various combinations of human activity, predation risk, and food abundance within the two habitats. These results provide insights into the in situ conservation of the threatened species within the context of global urbanization.